Pengaruh Praktik Total Quality Management terhadap Inovasi di Perguruan Tinggi - Firman - (Jurnal Kajian Manajemen Bisnis, 2012)
Total Quality Management (TQM) is a management philosophy of most organizations to improve the effectiveness and performance to become a world-class organization. The purpose of this study, using multiple regression analysis, was to test the effect of TQM practices of teamwork, autonomy and process control on innovation. The results of this study with sample size is 85 faculty and high school leaders in Yogyakarta show that autonomy and process control has a positive effect on innovation, while teamwork having no significant effect on innovation